Effects of Mindfulness-Based Cognitive Therapy on Peripheral Markers of Stress and Inflammation in Older-Adults With Depression and Anxiety: A Parallel Analysis of a Randomized Controlled Trial - Belliveau, Claudia; Nagy, Corina; Escobar, Sophia; Mechawar, Naguib; Turecki, Gustavo; Rej, Soham; Torres-Platas, Susana G. (Frontiers in Psychiatry, 2021)
Background: Depression and anxiety are prevalent in older-adults and often difficult to treat: up to 55% of patients are unresponsive to pharmacotherapy. Mindfulness-Based Cognitive Therapy (MBCT) is a promising treatment, however, its biological mechanisms remain unknown in older-adults. Methods: We examined if, in older-adults, decreased depression and anxiety symptoms after MBCT are associated with changes in the expression levels of C-reactive protein, Interleukin-1β, Monocyte chemoattractant protein-1 and mineralocorticoid receptor compared to treatment as usual (TAU). Older-adults (age ≥60) with depression and anxiety were randomized to MBCT or treatment as usual. Gene expression levels from blood samples were measured using quantitative polymerase chain reaction (n = 37) at baseline and after 8-weeks of MBCT or TAU. Results: As previously published, we found a significant reduction in symptoms of depression F (1, 35) = 10.68, p = 0.002, partial η2 = 0.23 and anxiety F (1, 35) = 9.36, p = 0.004, partial η2 = 0.21 in geriatric participants following MBCT compared to TAU. However, the expression levels of measured genes were not significantly different between groups and were not associated with changes in depression and anxiety symptoms. Conclusion: Our results suggest that the symptom reduction following MBCT in older-adults may not be accompanied by changes in the stress-response and inflammatory pathways. Future research should address other potential biological alterations associated to MBCT that may be responsible for the reduction of symptoms.